"FLIPPED CLASSROOM TYPE PEER INSTRUCTION-BASED LEARNING" BASED ON A WEBSITE TO IMPROVE STUDENT'S PROBLEM SOLVING - Tuti Azizah; Ahmad Fauzan; Yulyanti Harisman (Jurnal Infinity, 2022)
This study aims to develop learning tools in the form of lesson plans, student worksheets, learning videos, and PPT, based on WEB for first-grade seventh-school material linear equations with flipped classroom-type peer instruction. The development of this WEB-based learning tool uses the Plomp model. The steps for developing web-based learning tools include preliminary needs analysis, curriculum analysis, concept analysis, student analysis, and literature analysis. Then product development and assessment. This research was carried out during the product development stage based on needs analysis, curriculum analysis, concept analysis, student analysis, and literature analysis and then self-evaluated. The preliminary analysis obtained information that teachers need learning tools that can help students improve problem-solving skills, students need engaging learning media, students are interested in using learning media using videos with a period of 10-15 minutes, and PPT, accessed in the WEB. Then the product is compiled and evaluated on its own, related to the apparent error in using it. Based on the preliminary analysis, learning lessons, student worksheets, learning videos, PPT based on WEB and self-evaluation have been produced, which can then be validated by experts.